(3HjhdhLjG GdQjGVI h GdCOGA GdMQcjs - (3SdGeI HgGA GdOjf GHQGgjes ((3GdbGgQIs (3OGQ GdacQs, 1992)
(3GdYhGed h GdaQhb GdHjhdhLjI Hjf GdLfSjf GdJj JDKQ Ydi GdCOGA GdMQcj,h cPG HjhdhLjG JYde GdegGQGJ GdMQcjI, h GdLgGR GdYUHj h GdJOQjH GdQjGVj,Gdfeh h GdJWhQ,gVe h JeKjd GdZPGA haj GdCNjQ JWQb Gdi GdWGbI h GdJZPjI h GdgQehfGJ ,ceG CTGQ Gdi GdefTWGJ h NWhQJgG Ydi GdQjGVj(B.s
Keywords: (3GdJOQjH GdQjGVjs